Far-Infrared Radiation with Sauna Method Improves Recovery of Fatigue and Muscle Damage in Athletes After Submaximal Physical Exercise - Oce Wiriawan; Hari Setijono; Shidqi Hamdi Pratama Putera; Ghana Firsta Yosika; Arifah Kaharina; Anindya Mar’atus Sholikhah; Adi Pranoto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Muscle damage is one of the most frequent causes of decreased physical ability in training. Injuries during exercise are caused by damage to soft tissue, such as muscles. This can occur if recovery is inadequate in an exercise program. Incomplete recovery can reduce an athlete's performance. This study aims to determine the effect of far-infrared radiation (FIR) in improving fatigue and muscle cell damage in athletes after submaximal physical exercise. A total of 16 male athletes, aged 18-23 years were recruited to participate in the study and were given physical exercise at submaximal intensity (80% HRmax) for 30 minutes using a treadmill. The administration of FIR 45ºC was carried out immediately after submaximal intensity exercise for 30 minutes, while the recovery control group was carried out lying down without additional intervention. Measurement of fatigue levels uses the lactic acid (LA) parameter with the Accutrend Plus Meter, while measuring muscle cell damage uses the MDA level parameter using the Thiobarbituric acid reactive substance (TBARs) method. The data analysis technique uses the independent sample t-test with a significance level of 5%. The results showed that there was a significant difference in mean post-treatment LA between the control (CTR) vs. recovery group with FIR 45ºC for 30 minutes (EXP) 3.48±1.62 mmol/L vs. 3.48±1.62 mmol/L, p=0.035. Mean post-treatment MDA levels between CTR vs. EXP 0.45±0.19 ng/mL vs. 0.24±0.03 ng/mL, p=0.011. Far-infrared radiation using the sauna method has been proven effective in reducing lactic acid and MDA levels after submaximal physical exercise.